Corrosion-resistant glass fiber composite material and preparation method thereof

By using a hybrid control system during the preparation of glass fiber composite materials to accurately control the temperature and stirring parameters, the problem of uneven mixing during the traditional preparation process has been solved, and the material performance and quality of the material are significantly improved.

CN119331391AInactive Publication Date: 2025-01-21NANTONG QIANGZHENG COMPOSITE MATERIAL TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411497249.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the preparation of traditional glass fiber composite materials, the temperature and stirring control are inaccurate, resulting in uneven mixing of nucleating agents, affecting the performance and quality of the material.

Method used

Adopt an advanced hybrid control system, accurately control the temperature and stirring parameters, monitor the uniformity of stirring in real time, and ensure that the complex crystalline nucleus is mixed evenly.

Benefits of technology

High-quality composite material preparation is achieved, and the corrosion resistance, mechanical properties and service life of the material are improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a corrosion-resistant glass fiber composite material and a preparation method thereof, and the corrosion-resistant glass fiber composite material comprises the following components in parts by weight: 40-60 parts of phenolic epoxy vinyl ester resin, 25-30 parts of glass fibers, 5-7 parts of kailaff fibers, 5-7 parts of glass fiber chopped strand mats, 1-2 parts of bamboo fibers, 11-15 parts of a filling material, 2-4 parts of an antioxidant, 2-5 parts of diisononyl phthalate and 5-7 parts of a coupling agent. The filling material comprises the following components in parts by weight: 10-12 parts of aluminum oxide, 1-3 parts of carbon nanotubes and 1-2 parts of graphene, and the compound crystallization nucleating agent is prepared from the following components: talcum powder, aluminum sorbate, a silane coupling agent, a dispersing agent, a co-plasticizer and an ultraviolet light absorber. The invention relates to the technical field of preparation of glass fiber composite materials. According to the corrosion-resistant glass fiber composite material and the preparation method thereof, the corrosion-resistant glass fiber composite material has excellent corrosion resistance, good mechanical property and good processability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glass fiber composite material preparation, in particular to a corrosion-resistant glass fiber composite material and a preparation method thereof. Background Art

[0002] In the field of modern materials science, high-performance corrosion-resistant glass fiber composites have broad application prospects in many industrial fields due to their excellent performance. However, it is not easy to prepare corrosion-resistant glass fiber composites with excellent performance. The preparation of compound crystallization nucleating agents is one of the key links. In the traditional material preparation process, the control of temperature and stirring is often extensive, lacking precision and intelligence. This may lead to uneven mixing of the components of the nucleating agent, affecting the performance and quality of the final product. For example, unstable temperature may cause fluctuations in the chemical reaction rate and affect the crystallization effect of the nucleating agent; insufficient stirring may lead to uneven distribution of the components and reduce the corrosion resistance and other properties of the material. In addition, the monitoring of stirring uniformity is often neglected. Without effective monitoring means, it is difficult to ensure that the nucleating agent reaches an ideal mixing state during the preparation process. Uneven nucleating agents will form weak points in corrosion-resistant glass fiber composites, reducing the overall performance and service life of the material.

[0003] In order to solve these problems, it is imperative to develop an advanced mixing control system that can accurately control the temperature to ensure that the reaction is carried out under suitable temperature conditions; at the same time, it can flexibly adjust the stirring parameters to achieve full mixing of the components. In addition, by introducing a stirring uniformity monitoring method, the mixing state of the nucleating agent can be understood in real time, and the control parameters can be adjusted in time to prepare a high-quality compound crystalline nucleating agent, thereby providing a strong guarantee for the excellent performance of corrosion-resistant glass fiber composites. Summary of the invention

[0004] To achieve the above objectives, the present invention is implemented through the following technical scheme: a corrosion-resistant glass fiber composite material and a preparation method thereof, comprising the following components by weight: 40-60 parts of phenolic epoxy vinyl ester resin, 25-30 parts of glass fiber, 5-7 parts of Kevlar fiber, 5-7 parts of glass fiber chopped strand mat, 1-2 parts of bamboo fiber, 11-15 parts of filling material, 2-4 parts of antioxidant, 2-5 parts of diisononyl phthalate, 5-7 parts of coupling agent, 2-3 parts of hydroxymethyl cellulose and 3-6 parts of compound crystallization nucleating agent.

[0005] Preferably, the filling material comprises the following components by weight: 10-12 parts of aluminum oxide, 1-3 parts of carbon nanotubes, and 1-2 parts of graphene.

[0006] Preferably, the composite crystal nucleating agent is composed of the following ingredients: talc, aluminum sorbate, silane coupling agent, dispersant, co-plasticizer and ultraviolet absorber, wherein the ratio of talc, aluminum sorbate, silane coupling agent, dispersant, co-plasticizer and ultraviolet absorber is 2:5:4:6:5:2.

[0007] Preferably, the silane coupling agent is KH-550 and KH-560, the molar ratio of KH-550 to KH-560 is 2.09:1, the dispersant is any one or more of low molecular weight polyethylene wax and stearic acid, and the auxiliary plasticizer is sodium tripolyphosphate.

[0008] A method for preparing a corrosion-resistant glass fiber composite material comprises the following steps: Step S1: putting glass fiber, Kevlar fiber and glass fiber chopped strand mat into an oven for drying to remove moisture, the drying temperature is set to 110° C., the drying time is 2.5 hours, and after drying, the fiber material is stored in a sealed bag to obtain a raw material matrix A; Step S2: surface treating the raw material matrix A prepared in step S1 with a silane coupling agent, soaking the raw material matrix A in the silane coupling agent solution for 30 minutes, then taking it out and drying it, to obtain a raw material matrix B; Step S3: crushing the bamboo fiber to prepare 1-3 mm bamboo fiber, soaking the bamboo fiber in an alkaline solution for 2-3 hours to remove impurities and lignin in the bamboo fiber, and then washing the bamboo fiber with clean water until the pH value of the washing solution is neutral, and finally drying the bamboo fiber at a drying temperature of 80° C. to 90° C. for 2.5-3.5 hours; Step S4: adding aluminum oxide, carbon nanotubes and graphene to a dispersion medium and then placing them in an ultrasonic disperser, and adding sodium dodecylbenzene sulfonate as a surfactant, and performing a dispersion operation, with an ultrasonic power of 600-800 W and a dispersion time of 45-60 minutes; Step S5: adding phenolic epoxy vinyl ester resin to a reaction kettle, heating to 90° C., and when the material has fluidity, sequentially adding hydroxymethyl cellulose, diisononyl phthalate, antioxidant, and coupling agent, and stirring at a speed of 400-600 r / min for 40-60 minutes; Step S6: adding the dispersed alumina, carbon nanotubes, and graphene filling materials into the reactor, continuing to stir at a speed of 400-600 r / min for 25-30 minutes, then adding the composite crystal nucleating agent, and continuing to stir for 18-25 minutes; Step S7: adding the dried glass fiber, Kevlar fiber, glass fiber chopped strand mat and pretreated bamboo fiber into the reactor, while increasing the stirring speed to 900 r / min for 50-70 minutes; Step S8: pouring the mixed material into a mold and molding the material using a compression molding process.

[0009] Preferably, the dispersion medium in step S4 is ethanol, and the upper liquid level of ethanol is higher than the top of the mixture of aluminum oxide, carbon nanotubes and graphene, and the addition amount of sodium dodecylbenzene sulfonate is 0.5%-1% of the total mass of the filling material.

[0010] Preferably, the composite crystal nucleating agent in step S5 comprises the following preparation steps: Step A1: adding talcum powder and aluminum sorbate into a reaction kettle, stirring at 40° C. and 500 r / min for 10 minutes to preliminarily mix the two, and obtaining an intermediate nucleating agent B; Step A2: adding KH-550 and KH-560 silane coupling agents into the reaction kettle, stirring while adding, the adding time is controlled to be about 15 minutes, the mixing control system controls the temperature to be maintained at 40° C., the stirring speed remains unchanged, and stirring is continued for 20 minutes to allow the silane coupling agent to fully contact with talc and aluminum sorbate; Step A3: adding the dispersant and sodium tripolyphosphate into the reaction kettle, keeping the temperature constant, controlling the stirring speed to 800 r / min by the mixing control system, stirring for 25 minutes, and ensuring that the dispersant and the auxiliary plasticizer are evenly dispersed in the mixture; Step A4: Add the ultraviolet absorber into the reaction kettle, and continue stirring at 60°C and 800r / min for 15 minutes to fully integrate the ultraviolet absorber into the mixture to obtain a composite crystal nucleating agent.

[0011] Preferably, the mixing control system includes a temperature control module, a stirring control module, a component monitoring module, an intelligent control module and an alarm module, the temperature control module includes a temperature detector, a heating mechanism and a cooling mechanism, the stirring control module includes a motor and a speed regulation mechanism and a stirring mechanism, the component detection module is composed of a component detector, the intelligent control module includes a data processing unit and a control instruction unit, and the alarm module includes a sensor fault detection unit and an alarm.

[0012] Preferably, the specific control method of the hybrid control system is as follows: Step 1: When talcum powder and aluminum sorbate are mixed, the temperature of the reactor is set to 40°C, the intelligent control module starts the heating device, and the temperature of the reactor is gradually increased to 40°C. The temperature detector feeds back the temperature data in real time. When the temperature reaches 40°C, the control system maintains the heating power stable to compensate for the heat loss and keep the temperature constant. The stirring device is started at a speed of 500r / min, and the stirring is continued for 10 minutes to make the two preliminarily mixed evenly. During this process, the temperature and stirring speed are monitored in real time to stabilize them at the set value. At the same time, the component detector starts to work to monitor the stirring uniformity; Step 2: When adding KH-550 and KH-560 silane coupling agents, stir while adding, control the adding time to 15 minutes, keep the temperature of the reactor at 40°C, keep the stirring speed unchanged, and continue stirring for 20 minutes to allow the silane coupling agent to fully contact with talcum powder and aluminum sorbate. During this period, the temperature sensor continuously monitors the temperature. If the temperature deviates, such as higher than 40°C, the control system immediately starts the cooling device to reduce the heating power so that the temperature gradually returns to 40°C; if the temperature is lower than 40°C, the control system increases the heating power to ensure that the temperature is stable at 40°C. The temperature sensor and the speed sensor provide real-time feedback data, and if there is any deviation, it is adjusted in time. The component sensor continuously monitors the stirring uniformity, and the control system adjusts the stirring parameters if necessary; Step 3: Add dispersant and sodium tripolyphosphate to the reactor, keep the temperature at 40°C, increase the stirring speed to 800r / min, and stir for 25 minutes. During this process, mix and stir by increasing the stirring speed to make the dispersant and co-plasticizer evenly dispersed in the mixture, while paying close attention to the stability of temperature and speed. The temperature control method is the same as step 2, and the component sensor continuously monitors the stirring uniformity.

[0013] Step 4: Add the UV absorber to the reactor and raise the temperature to 60°C. The intelligent control module gradually increases the heating power to raise the temperature from 40°C to 60°C. The temperature detector monitors the temperature change in real time. When the temperature reaches 60°C, the control system adjusts the heating power to maintain the temperature stability and continues to stir at a speed of 800r / min for 15 minutes to fully integrate the UV absorber into the mixture. At this stage, the temperature and stirring speed are also monitored in real time to ensure that they meet the set requirements. The component sensor continuously monitors the stirring uniformity.

[0014] The present invention provides a corrosion-resistant glass fiber composite material and a preparation method thereof, which has the following beneficial effects: Excellent corrosion resistance: Phenolic epoxy vinyl ester resin itself has good corrosion resistance. When combined with reinforcing materials such as glass fiber, Kevlar fiber, and bamboo fiber, the composite material structure is stable and can effectively resist the erosion of chemical substances such as acid, alkali, and salt. It can still maintain good performance in harsh chemical environments, extending the service life of the material and is suitable for various scenarios with corrosive media.

[0015] Good mechanical properties: High strength: Glass fiber is an excellent reinforcement material with high tensile strength and elastic modulus, which can significantly improve the strength of composite materials. Keraflo fiber has high strength and high modulus, and works synergistically with glass fiber to further enhance the overall strength of the material, enabling it to withstand greater loads and can be used in structural parts with high material strength requirements1.

[0016] High toughness: The addition of bamboo fiber increases the toughness of the material, enabling the composite material to absorb energy when impacted by external forces, reducing the generation and expansion of cracks and improving the impact resistance of the material.

[0017] Lighter weight: Compared with traditional metal materials, glass fiber composite materials have lower density and lighter weight, making them easier to handle, install and transport. They have obvious advantages in some fields that have strict requirements on weight, such as aerospace, automobiles, etc.

[0018] Good processing performance: The composite material can be formed by a variety of processing methods, such as molding, injection molding, winding, etc., and can be manufactured into products of various shapes and sizes according to different application requirements to meet the design requirements of complex structures.

[0019] Good thermal stability: At higher temperatures, the composite material can still maintain good performance stability, is not prone to deformation, softening, etc., and can be used normally within a certain temperature range.

[0020] Electrical insulation: Glass fiber composite materials have good electrical insulation properties and can be used in electrical, electronic and other fields that require high insulation properties.

[0021] Versatile filling material enhancements: Enhanced hardness: Alumina, as a filling material, has a high hardness and can increase the hardness and wear resistance of the composite material and improve the surface finish of the material.

[0022] Unique nanomaterial properties: Carbon nanotubes and graphene have excellent mechanical properties, electrical conductivity and thermal conductivity. They can form a three-dimensional network structure in composite materials, enhance the strength, toughness and thermal conductivity of the material, and improve the material's anti-aging and flame retardant properties.

[0023] Synergistic effect of functional additives: Antioxidant: It can prevent the material from being oxidized during processing and use, maintain the stability of the material's performance and extend the material's service life.

[0024] Diisononyl phthalate: As a plasticizer, it can increase the flexibility and plasticity of the material, making it easier to process and shape.

[0025] Coupling agent: can improve the interfacial bonding between the reinforcing material and the resin and improve the overall performance of the composite material.

[0026] Hydroxymethyl cellulose: It can improve the viscosity and stability of the material and help the molding and processing of the material.

[0027] Compound crystallization nucleating agent: can promote the crystallization of resin, improve the crystallinity and heat resistance of materials, and improve the mechanical properties and processing properties of materials. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0029] In the first embodiment, the present invention provides a technical solution: a corrosion-resistant glass fiber composite material, comprising the following weight components: 40 parts of phenolic epoxy vinyl ester resin, 25 parts of glass fiber, 5 parts of Kevlar fiber, 5 parts of glass fiber chopped strand mat, 1 part of bamboo fiber, 11 parts of filler material, 2 parts of antioxidant, 2 parts of diisononyl phthalate, 5 parts of coupling agent, 2 parts of hydroxymethyl cellulose and 3 parts of compound crystal nucleating agent, the filler material comprises the following weight components: 10 parts of alumina, 1 part of carbon nanotubes, 1 part of graphene, the compound crystal nucleating agent The core agent is composed of the following ingredients: talc, aluminum sorbate, silane coupling agent, dispersant, co-plasticizer and ultraviolet absorber, wherein the ratio of talc, aluminum sorbate, silane coupling agent, dispersant, co-plasticizer and ultraviolet absorber is 2:5:4:6:5:2, the silane coupling agent is KH-550 and KH-560, the molar ratio of KH-550 to KH-560 is 2.09:1, the dispersant is any one or more of low molecular weight polyethylene wax and stearic acid, and the co-plasticizer is sodium tripolyphosphate.

[0030] A method for preparing a corrosion-resistant glass fiber composite material comprises the following steps: Step S1: putting glass fiber, Kevlar fiber and glass fiber chopped strand mat into an oven for drying to remove moisture, the drying temperature is set to 110° C., the drying time is 2.5 hours, and after drying, the fiber material is stored in a sealed bag to obtain a raw material matrix A; Step S2: surface treating the raw material matrix A prepared in step S1 with a silane coupling agent, soaking the raw material matrix A in the silane coupling agent solution for 30 minutes, then taking it out and drying it, to obtain a raw material matrix B; Step S3: crushing the bamboo fiber to prepare 1 mm bamboo fiber, soaking the bamboo fiber in an alkaline solution for 2 hours to remove impurities and lignin in the bamboo fiber, and then washing the bamboo fiber with clean water until the pH value of the washing solution is neutral, and finally drying the bamboo fiber at a drying temperature of 80°C for 2.5 hours; Step S4: adding aluminum oxide, carbon nanotubes and graphene to a dispersion medium and then placing them in an ultrasonic disperser, and adding sodium dodecylbenzene sulfonate as a surfactant, and performing a dispersion operation, the ultrasonic power is 600 W, the dispersion time is 45 minutes, the dispersion medium is ethanol, and the upper liquid level of ethanol is higher than the top of the mixture of aluminum oxide, carbon nanotubes and graphene, and the addition amount of the sodium dodecylbenzene sulfonate is 0.5% of the total mass of the filling material; Step S5: adding phenolic epoxy vinyl ester resin to a reaction kettle, heating to 90° C., and when the material has fluidity, sequentially adding hydroxymethyl cellulose, diisononyl phthalate, antioxidant, and coupling agent, and stirring at a speed of 400 r / min for 40 minutes. The composite crystal nucleating agent comprises the following preparation steps: Step A1: adding talcum powder and aluminum sorbate into a reaction kettle, stirring at 40° C. and 500 r / min for 10 minutes to preliminarily mix the two, and obtaining an intermediate nucleating agent B; Step A2: adding KH-550 and KH-560 silane coupling agents into the reaction kettle, stirring while adding, the adding time is controlled to be about 15 minutes, the mixing control system controls the temperature to be maintained at 40° C., the stirring speed remains unchanged, and stirring is continued for 20 minutes to allow the silane coupling agent to fully contact with talc and aluminum sorbate; Step A3: adding the dispersant and sodium tripolyphosphate into the reaction kettle, keeping the temperature constant, controlling the stirring speed to 800 r / min by the mixing control system, stirring for 25 minutes, and ensuring that the dispersant and the auxiliary plasticizer are evenly dispersed in the mixture; Step A4: adding the ultraviolet absorber into the reaction kettle, and continuing to stir at a temperature of 60° C. and a speed of 800 r / min for 15 minutes to fully blend the ultraviolet absorber into the mixture to obtain a composite crystal nucleating agent; Step S6: adding the dispersed alumina, carbon nanotubes and graphene filling materials into the reactor, continuing to stir at a speed of 400 r / min for 25 minutes, then adding the composite crystal nucleating agent, and continuing to stir for 18-25 minutes; Step S7: adding the dried glass fiber, Kevlar fiber, glass fiber chopped mat and pretreated bamboo fiber into the reactor, while increasing the stirring speed to 900 r / min for 50 minutes; Step S8: pouring the mixed material into a mold and molding the material using a compression molding process.

[0031] The mixing control system includes a temperature control module, a stirring control module, a component monitoring module, an intelligent control module and an alarm module. The temperature control module includes a temperature detector, a heating mechanism and a cooling mechanism. The stirring control module includes a motor and a speed regulation mechanism and a stirring mechanism. The component detection module is composed of a component detector. The intelligent control module includes a data processing unit and a control instruction unit. The alarm module includes a sensor fault detection unit and an alarm.

[0032] The specific control method of the hybrid control system is as follows: Step 1: When talcum powder and aluminum sorbate are mixed, the temperature of the reactor is set to 40°C, the intelligent control module starts the heating device, and the temperature of the reactor is gradually increased to 40°C. The temperature detector feeds back the temperature data in real time. When the temperature reaches 40°C, the control system maintains the heating power stable to compensate for the heat loss and keep the temperature constant. The stirring device is started at a speed of 500r / min, and the stirring is continued for 10 minutes to make the two preliminarily mixed evenly. During this process, the temperature and stirring speed are monitored in real time to stabilize them at the set value. At the same time, the component detector starts to work to monitor the stirring uniformity; Step 2: When adding KH-550 and KH-560 silane coupling agents, stir while adding, control the adding time to 15 minutes, keep the temperature of the reactor at 40°C, keep the stirring speed unchanged, and continue stirring for 20 minutes to allow the silane coupling agent to fully contact with talcum powder and aluminum sorbate. During this period, the temperature sensor continuously monitors the temperature. If the temperature deviates, such as higher than 40°C, the control system immediately starts the cooling device to reduce the heating power so that the temperature gradually returns to 40°C; if the temperature is lower than 40°C, the control system increases the heating power to ensure that the temperature is stable at 40°C. The temperature sensor and the speed sensor provide real-time feedback data, and if there is any deviation, it is adjusted in time. The component sensor continuously monitors the stirring uniformity, and the control system adjusts the stirring parameters if necessary; Step 3: Add dispersant and sodium tripolyphosphate to the reactor, keep the temperature at 40°C, increase the stirring speed to 800r / min, and stir for 25 minutes. During this process, mix and stir by increasing the stirring speed to make the dispersant and co-plasticizer evenly dispersed in the mixture, while paying close attention to the stability of temperature and speed. The temperature control method is the same as step 2, and the component sensor continuously monitors the stirring uniformity.

[0033] Step 4: Add the UV absorber to the reactor and raise the temperature to 60°C. The intelligent control module gradually increases the heating power to raise the temperature from 40°C to 60°C. The temperature detector monitors the temperature change in real time. When the temperature reaches 60°C, the control system adjusts the heating power to maintain the temperature stability and continues to stir at a speed of 800r / min for 15 minutes to fully integrate the UV absorber into the mixture. At this stage, the temperature and stirring speed are also monitored in real time to ensure that they meet the set requirements. The component sensor continuously monitors the stirring uniformity.

[0034] In step 2, when adding KH-550 and KH-560 silane coupling agents, stir while adding and continuously monitor the stirring uniformity. If the component sensor detects that the difference in component concentration at each position exceeds the allowable range (such as the difference value is greater than 5%), or during the stirring process, it is found that the stirring time has reached the preset 20 minutes but the stirring uniformity has not reached a good state (that is, the difference in component concentration detected by each sensor is within the set allowable range), the stirring parameters need to be adjusted.

[0035] At the same time, if the temperature feedback from the temperature sensor shows a large deviation and is adjusted back to the set 40°C through the heating or cooling device within 5 minutes, it may also affect the stirring effect, and it is necessary to consider adjusting the stirring parameters.

[0036] The specific adjustment strategies are as follows: (1) Adjust the stirring speed: If the mixing uniformity is poor, the mixing speed can be increased, but the increased speed should not exceed 900r / min to avoid excessive burden on the equipment or causing problems such as splashing of the mixture; After increasing the stirring speed, continue to monitor the stirring uniformity and temperature changes. If the stirring uniformity is improved and the temperature can be stabilized at around 40°C, continue stirring for a period of time, usually 10 minutes, at the new stirring speed to ensure adequate mixing; If good stirring uniformity cannot be achieved after increasing the stirring speed, you can try to increase the speed gradually, but the increase should not be too large each time, and pay close attention to the temperature and equipment operating status.

[0037] (2) Adjust the mixing time: If the mixing uniformity is still not up to standard after the scheduled 20-minute mixing time, the mixing time can be appropriately extended by 5 minutes; During the process of extending the stirring time, the stirring uniformity and temperature are continuously monitored. If the stirring uniformity gradually improves, it can be decided whether to continue to extend the stirring time or maintain the current state until good stirring uniformity is achieved according to the actual situation; If the stirring uniformity is still poor after extending the stirring time, it is necessary to consider adjusting the stirring speed and other possible factors.

[0038] (3) Adjust stirring parameters according to temperature: If the temperature deviation is large and affects the stirring effect, you can further optimize the temperature control while adjusting the stirring parameters. If the temperature is too high, you can increase the power of the cooling device or reduce the heating power; if the temperature is too low, you can increase the heating power; According to the temperature changes, adjust the stirring speed and stirring time in time. When the temperature is high, the stirring speed can be appropriately reduced to reduce heat generation. When the temperature is low, the stirring speed can be appropriately increased to promote mixing and heat transfer.

[0039] In the second embodiment, the present invention provides a technical solution: a corrosion-resistant glass fiber composite material, comprising the following weight components: 50 parts of phenolic epoxy vinyl ester resin, 27 parts of glass fiber, 6 parts of Kevlar fiber, 6 parts of glass fiber chopped strand mat, 1.5 parts of bamboo fiber, 13 parts of filler material, 3 parts of antioxidant, 3.5 parts of diisononyl phthalate, 6 parts of coupling agent, 2.5 parts of hydroxymethyl cellulose and 4.5 parts of compound crystal nucleating agent, the filler material comprises the following weight components: 1011 parts of alumina, 12 parts of carbon nanotubes, 1.5 parts of graphene, the The composite crystal nucleating agent is composed of the following ingredients: talc, aluminum sorbate, silane coupling agent, dispersant, co-plasticizer and ultraviolet absorber, wherein the ratio of talc, aluminum sorbate, silane coupling agent, dispersant, co-plasticizer and ultraviolet absorber is 2:5:4:6:5:2, the silane coupling agent is KH-550 and KH-560, the molar ratio of KH-550 to KH-560 is 2.09:1, the dispersant is any one or more of low molecular weight polyethylene wax and stearic acid, and the co-plasticizer is sodium tripolyphosphate.

[0040] A method for preparing a corrosion-resistant glass fiber composite material comprises the following steps: Step S1: putting glass fiber, Kevlar fiber and glass fiber chopped strand mat into an oven for drying to remove moisture, the drying temperature is set to 110° C., the drying time is 2.5 hours, and after drying, the fiber material is stored in a sealed bag to obtain a raw material matrix A; Step S2: surface treating the raw material matrix A prepared in step S1 with a silane coupling agent, soaking the raw material matrix A in the silane coupling agent solution for 30 minutes, then taking it out and drying it, to obtain a raw material matrix B; Step S3: crushing the bamboo fiber to prepare 2 mm bamboo fiber, soaking the bamboo fiber in an alkaline solution for 2 hours to remove impurities and lignin in the bamboo fiber, and then washing the bamboo fiber with water until the pH value of the washing solution is neutral, and finally drying the bamboo fiber at a drying temperature of 80° C. for 2.5 hours; Step S4: adding aluminum oxide, carbon nanotubes and graphene to a dispersion medium and then placing them in an ultrasonic disperser, and adding sodium dodecylbenzene sulfonate as a surfactant, and performing a dispersion operation, the ultrasonic power is 600 W, the dispersion time is 45 minutes, the dispersion medium is ethanol, and the upper liquid level of ethanol is higher than the top of the mixture of aluminum oxide, carbon nanotubes and graphene, and the addition amount of the sodium dodecylbenzene sulfonate is 0.5% of the total mass of the filling material; Step S5: adding phenolic epoxy vinyl ester resin to a reaction kettle, heating to 90° C., and when the material has fluidity, sequentially adding hydroxymethyl cellulose, diisononyl phthalate, antioxidant, and coupling agent, and stirring at a speed of 400 r / min for 40 minutes. The composite crystal nucleating agent comprises the following preparation steps: Step A1: adding talcum powder and aluminum sorbate into a reaction kettle, stirring at 40° C. and 500 r / min for 10 minutes to preliminarily mix the two, and obtaining an intermediate nucleating agent B; Step A2: adding KH-550 and KH-560 silane coupling agents into the reaction kettle, stirring while adding, the adding time is controlled to be about 15 minutes, the mixing control system controls the temperature to be maintained at 40° C., the stirring speed remains unchanged, and stirring is continued for 20 minutes to allow the silane coupling agent to fully contact with talc and aluminum sorbate; Step A3: adding the dispersant and sodium tripolyphosphate into the reaction kettle, keeping the temperature constant, controlling the stirring speed to 800 r / min by the mixing control system, stirring for 25 minutes, and ensuring that the dispersant and the auxiliary plasticizer are evenly dispersed in the mixture; Step A4: adding the ultraviolet absorber into the reaction kettle, and continuing to stir at a temperature of 60° C. and a speed of 800 r / min for 15 minutes to fully blend the ultraviolet absorber into the mixture to obtain a composite crystal nucleating agent; Step S6: adding the dispersed alumina, carbon nanotubes, and graphene filling materials into the reactor, continuing to stir at a speed of 400 r / min for 25 minutes, then adding the composite crystal nucleating agent, and continuing to stir for 18 minutes; Step S7: adding the dried glass fiber, Kevlar fiber, glass fiber chopped mat and pretreated bamboo fiber into the reactor, while increasing the stirring speed to 900 r / min for 50 minutes; Step S8: pouring the mixed material into a mold and molding the material using a compression molding process.

[0041] The mixing control system includes a temperature control module, a stirring control module, a component monitoring module, an intelligent control module and an alarm module. The temperature control module includes a temperature detector, a heating mechanism and a cooling mechanism. The stirring control module includes a motor and a speed regulation mechanism and a stirring mechanism. The component detection module is composed of a component detector. The intelligent control module includes a data processing unit and a control instruction unit. The alarm module includes a sensor fault detection unit and an alarm.

[0042] The specific control method of the hybrid control system is as follows: Step 1: When talcum powder and aluminum sorbate are mixed, the temperature of the reactor is set to 40°C, the intelligent control module starts the heating device, and the temperature of the reactor is gradually increased to 40°C. The temperature detector feeds back the temperature data in real time. When the temperature reaches 40°C, the control system maintains the heating power stable to compensate for the heat loss and keep the temperature constant. The stirring device is started at a speed of 500r / min, and the stirring is continued for 10 minutes to make the two preliminarily mixed evenly. During this process, the temperature and stirring speed are monitored in real time to stabilize them at the set value. At the same time, the component detector starts to work to monitor the stirring uniformity; Step 2: When adding KH-550 and KH-560 silane coupling agents, stir while adding, control the adding time to 15 minutes, keep the temperature of the reactor at 40°C, keep the stirring speed unchanged, and continue stirring for 20 minutes to allow the silane coupling agent to fully contact with talcum powder and aluminum sorbate. During this period, the temperature sensor continuously monitors the temperature. If the temperature deviates, such as higher than 40°C, the control system immediately starts the cooling device to reduce the heating power so that the temperature gradually returns to 40°C; if the temperature is lower than 40°C, the control system increases the heating power to ensure that the temperature is stable at 40°C. The temperature sensor and the speed sensor provide real-time feedback data, and if there is any deviation, it is adjusted in time. The component sensor continuously monitors the stirring uniformity, and the control system adjusts the stirring parameters if necessary; Step 3: Add dispersant and sodium tripolyphosphate to the reactor, keep the temperature at 40°C, increase the stirring speed to 800r / min, and stir for 25 minutes. During this process, mix and stir by increasing the stirring speed to make the dispersant and co-plasticizer evenly dispersed in the mixture, while paying close attention to the stability of temperature and speed. The temperature control method is the same as step 2, and the component sensor continuously monitors the stirring uniformity.

[0043] Step 4: Add the UV absorber to the reactor and raise the temperature to 60°C. The intelligent control module gradually increases the heating power to raise the temperature from 40°C to 60°C. The temperature detector monitors the temperature change in real time. When the temperature reaches 60°C, the control system adjusts the heating power to maintain the temperature stability and continues to stir at a speed of 800r / min for 15 minutes to fully integrate the UV absorber into the mixture. At this stage, the temperature and stirring speed are also monitored in real time to ensure that they meet the set requirements. The component sensor continuously monitors the stirring uniformity.

[0044] In step 2, when adding KH-550 and KH-560 silane coupling agents, stir while adding and continuously monitor the stirring uniformity. If the component sensor detects that the difference in component concentration at each position exceeds the allowable range (such as the difference value is greater than 5%), or during the stirring process, it is found that the stirring time has reached the preset 20 minutes but the stirring uniformity has not reached a good state (that is, the difference in component concentration detected by each sensor is within the set allowable range), the stirring parameters need to be adjusted.

[0045] At the same time, if the temperature feedback from the temperature sensor shows a large deviation and is adjusted back to the set 40°C through the heating or cooling device within 5 minutes, it may also affect the stirring effect, and it is necessary to consider adjusting the stirring parameters.

[0046] The specific adjustment strategies are as follows: (1) Adjust the stirring speed: If the mixing uniformity is poor, the mixing speed can be increased, but the increased speed should not exceed 900r / min to avoid excessive burden on the equipment or causing problems such as splashing of the mixture; After increasing the stirring speed, continue to monitor the stirring uniformity and temperature changes. If the stirring uniformity is improved and the temperature can be stabilized at around 40°C, continue stirring for a period of time, usually 10 minutes, at the new stirring speed to ensure adequate mixing; If good stirring uniformity cannot be achieved after increasing the stirring speed, you can try to increase the speed gradually, but the increase should not be too large each time, and pay close attention to the temperature and equipment operating status.

[0047] (2) Adjust the mixing time: If the mixing uniformity is still not up to standard after the scheduled 20-minute mixing time, the mixing time can be appropriately extended by 5 minutes; During the process of extending the stirring time, the stirring uniformity and temperature are continuously monitored. If the stirring uniformity gradually improves, it can be decided whether to continue to extend the stirring time or maintain the current state until good stirring uniformity is achieved according to the actual situation; If the stirring uniformity is still poor after extending the stirring time, it is necessary to consider adjusting the stirring speed and other possible factors.

[0048] (3) Adjust stirring parameters according to temperature: If the temperature deviation is large and affects the stirring effect, you can further optimize the temperature control while adjusting the stirring parameters. If the temperature is too high, you can increase the power of the cooling device or reduce the heating power; if the temperature is too low, you can increase the heating power; According to the temperature changes, adjust the stirring speed and stirring time in time. When the temperature is high, the stirring speed can be appropriately reduced to reduce heat generation. When the temperature is low, the stirring speed can be appropriately increased to promote mixing and heat transfer.

[0049] In the third embodiment, the present invention provides a technical solution: a corrosion-resistant glass fiber composite material, comprising the following weight components: 60 parts of phenolic epoxy vinyl ester resin, 30 parts of glass fiber, 7 parts of Kevlar fiber, 7 parts of glass fiber chopped strand mat, 2 parts of bamboo fiber, 15 parts of filler material, 4 parts of antioxidant, 5 parts of diisononyl phthalate, 7 parts of coupling agent, 3 parts of hydroxymethyl cellulose and 6 parts of compound crystal nucleating agent, the filling material comprises the following weight components: 12 parts of alumina, 3 parts of carbon nanotubes, 2 parts of graphene, the compound crystal nucleating agent The core agent is composed of the following ingredients: talc, aluminum sorbate, silane coupling agent, dispersant, co-plasticizer and ultraviolet absorber, wherein the ratio of talc, aluminum sorbate, silane coupling agent, dispersant, co-plasticizer and ultraviolet absorber is 2:5:4:6:5:2, the silane coupling agent is KH-550 and KH-560, the molar ratio of KH-550 to KH-560 is 2.09:1, the dispersant is any one or more of low molecular weight polyethylene wax and stearic acid, and the co-plasticizer is sodium tripolyphosphate.

[0050] A method for preparing a corrosion-resistant glass fiber composite material comprises the following steps: Step S1: putting glass fiber, Kevlar fiber and glass fiber chopped strand mat into an oven for drying to remove moisture, the drying temperature is set to 110° C., the drying time is 2.5 hours, and after drying, the fiber material is stored in a sealed bag to obtain a raw material matrix A; Step S2: surface treating the raw material matrix A prepared in step S1 with a silane coupling agent, soaking the raw material matrix A in the silane coupling agent solution for 30 minutes, then taking it out and drying it, to obtain a raw material matrix B; Step S3: crushing the bamboo fiber to prepare 3 mm bamboo fiber, soaking the bamboo fiber in an alkaline solution for 3 hours to remove impurities and lignin in the bamboo fiber, and then washing the bamboo fiber with clean water until the pH value of the washing solution is neutral, and finally drying the bamboo fiber at a drying temperature of 90° C. for 3.5 hours; Step S4: adding aluminum oxide, carbon nanotubes and graphene to a dispersion medium and then placing them in an ultrasonic disperser, and adding sodium dodecylbenzene sulfonate as a surfactant, and performing a dispersion operation, the ultrasonic power is 800 W, the dispersion time is 60 minutes, the dispersion medium is ethanol, and the upper liquid level of ethanol is higher than the top of the mixture of aluminum oxide, carbon nanotubes and graphene, and the addition amount of the sodium dodecylbenzene sulfonate is 1% of the total mass of the filling material; Step S5: adding phenolic epoxy vinyl ester resin to a reaction kettle, heating to 90° C., and when the material has fluidity, sequentially adding hydroxymethyl cellulose, diisononyl phthalate, antioxidant, and coupling agent, and stirring at a speed of 600 r / min for 60 minutes. The composite crystal nucleating agent comprises the following preparation steps: Step A1: adding talcum powder and aluminum sorbate into a reaction kettle, stirring at 40° C. and 500 r / min for 10 minutes to preliminarily mix the two, and obtaining an intermediate nucleating agent B; Step A2: adding KH-550 and KH-560 silane coupling agents into the reaction kettle, stirring while adding, the adding time is controlled to be about 15 minutes, the mixing control system controls the temperature to be maintained at 40° C., the stirring speed remains unchanged, and stirring is continued for 20 minutes to allow the silane coupling agent to fully contact with talc and aluminum sorbate; Step A3: adding the dispersant and sodium tripolyphosphate into the reaction kettle, keeping the temperature constant, controlling the stirring speed to 800 r / min by the mixing control system, stirring for 25 minutes, and ensuring that the dispersant and the auxiliary plasticizer are evenly dispersed in the mixture; Step A4: adding the ultraviolet absorber into the reaction kettle, and continuing to stir at a temperature of 60° C. and a speed of 800 r / min for 15 minutes to fully blend the ultraviolet absorber into the mixture to obtain a composite crystal nucleating agent; Step S6: adding the dispersed alumina, carbon nanotubes and graphene filling materials into the reactor, continuing to stir at a speed of 600 r / min for 30 minutes, then adding the composite crystal nucleating agent, and continuing to stir for 18-25 minutes; Step S7: adding the dried glass fiber, Kevlar fiber, glass fiber chopped strand mat and pretreated bamboo fiber into the reactor, while increasing the stirring speed to 900 r / min for 70 minutes; Step S8: pouring the mixed material into a mold and molding the material using a compression molding process.

[0051] The mixing control system includes a temperature control module, a stirring control module, a component monitoring module, an intelligent control module and an alarm module. The temperature control module includes a temperature detector, a heating mechanism and a cooling mechanism. The stirring control module includes a motor and a speed regulation mechanism and a stirring mechanism. The component detection module is composed of a component detector. The intelligent control module includes a data processing unit and a control instruction unit. The alarm module includes a sensor fault detection unit and an alarm.

[0052] The specific control method of the hybrid control system is as follows: Step 1: When talcum powder and aluminum sorbate are mixed, the temperature of the reactor is set to 40°C, the intelligent control module starts the heating device, and the temperature of the reactor is gradually increased to 40°C. The temperature detector feeds back the temperature data in real time. When the temperature reaches 40°C, the control system maintains the heating power stable to compensate for the heat loss and keep the temperature constant. The stirring device is started at a speed of 500r / min, and the stirring is continued for 10 minutes to make the two preliminarily mixed evenly. During this process, the temperature and stirring speed are monitored in real time to stabilize them at the set value. At the same time, the component detector starts to work to monitor the stirring uniformity; Step 2: When adding KH-550 and KH-560 silane coupling agents, stir while adding, control the adding time to 15 minutes, keep the temperature of the reactor at 40°C, keep the stirring speed unchanged, and continue stirring for 20 minutes to allow the silane coupling agent to fully contact with talcum powder and aluminum sorbate. During this period, the temperature sensor continuously monitors the temperature. If the temperature deviates, such as higher than 40°C, the control system immediately starts the cooling device to reduce the heating power so that the temperature gradually returns to 40°C; if the temperature is lower than 40°C, the control system increases the heating power to ensure that the temperature is stable at 40°C. The temperature sensor and the speed sensor provide real-time feedback data, and if there is any deviation, it is adjusted in time. The component sensor continuously monitors the stirring uniformity, and the control system adjusts the stirring parameters if necessary; Step 3: Add dispersant and sodium tripolyphosphate to the reactor, keep the temperature at 40°C, increase the stirring speed to 800r / min, and stir for 25 minutes. During this process, mix and stir by increasing the stirring speed to make the dispersant and co-plasticizer evenly dispersed in the mixture, while paying close attention to the stability of temperature and speed. The temperature control method is the same as step 2, and the component sensor continuously monitors the stirring uniformity.

[0053] Step 4: Add the UV absorber to the reactor and raise the temperature to 60°C. The intelligent control module gradually increases the heating power to raise the temperature from 40°C to 60°C. The temperature detector monitors the temperature change in real time. When the temperature reaches 60°C, the control system adjusts the heating power to maintain the temperature stability and continues to stir at a speed of 800r / min for 15 minutes to fully integrate the UV absorber into the mixture. At this stage, the temperature and stirring speed are also monitored in real time to ensure that they meet the set requirements. The component sensor continuously monitors the stirring uniformity.

[0054] In step 2, when adding KH-550 and KH-560 silane coupling agents, stir while adding and continuously monitor the stirring uniformity. If the component sensor detects that the difference in component concentration at each position exceeds the allowable range (such as the difference value is greater than 5%), or during the stirring process, it is found that the stirring time has reached the preset 20 minutes but the stirring uniformity has not reached a good state (that is, the difference in component concentration detected by each sensor is within the set allowable range), the stirring parameters need to be adjusted.

[0055] At the same time, if the temperature feedback from the temperature sensor shows a large deviation and is adjusted back to the set 40°C through the heating or cooling device within 5 minutes, it may also affect the stirring effect, and it is necessary to consider adjusting the stirring parameters.

[0056] The specific adjustment strategies are as follows: (1) Adjust the stirring speed: If the mixing uniformity is poor, the mixing speed can be increased, but the increased speed should not exceed 900r / min to avoid excessive burden on the equipment or causing problems such as splashing of the mixture; After increasing the stirring speed, continue to monitor the stirring uniformity and temperature changes. If the stirring uniformity is improved and the temperature can be stabilized at around 40°C, continue stirring for a period of time, usually 15 minutes, to ensure sufficient mixing; If good stirring uniformity cannot be achieved after increasing the stirring speed, you can try to increase the speed gradually, but the increase should not be too large each time, and pay close attention to the temperature and equipment operating status.

[0057] (2) Adjust the mixing time: If the mixing uniformity is still not up to standard after the scheduled 20-minute mixing time, the mixing time can be appropriately extended by 10 minutes; During the process of extending the stirring time, the stirring uniformity and temperature are continuously monitored. If the stirring uniformity gradually improves, it can be decided whether to continue to extend the stirring time or maintain the current state until good stirring uniformity is achieved according to the actual situation; If the stirring uniformity is still poor after extending the stirring time, it is necessary to consider adjusting the stirring speed and other possible factors.

[0058] (3) Adjust stirring parameters according to temperature: If the temperature deviation is large and affects the stirring effect, you can further optimize the temperature control while adjusting the stirring parameters. If the temperature is too high, you can increase the power of the cooling device or reduce the heating power; if the temperature is too low, you can increase the heating power; According to the temperature changes, adjust the stirring speed and stirring time in time. When the temperature is high, the stirring speed can be appropriately reduced to reduce heat generation. When the temperature is low, the stirring speed can be appropriately increased to promote mixing and heat transfer.

[0059] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field and related fields without creative work should fall within the scope of protection of the present invention. The structures, devices and operating methods not specifically described and explained in the present invention are implemented according to the conventional means in the field unless otherwise specified and limited.

Claims

1. A corrosion-resistant glass fiber composite material, characterized in that: The invention comprises the following components by weight: 40-60 parts of phenolic epoxy vinyl ester resin, 25-30 parts of glass fiber, 5-7 parts of Kevlar fiber, 5-7 parts of glass fiber chopped strand mat, 1-2 parts of bamboo fiber, 11-15 parts of filling material, 2-4 parts of antioxidant, 2-5 parts of diisononyl phthalate, 5-7 parts of coupling agent, 2-3 parts of hydroxymethyl cellulose and 3-6 parts of compound crystal nucleating agent.

2. The corrosion-resistant glass fiber composite material according to claim 1, characterized in that: The filling material comprises the following components by weight: 10-12 parts of aluminum oxide, 1-3 parts of carbon nanotubes, and 1-2 parts of graphene.

3. The corrosion-resistant glass fiber composite material according to claim 1, characterized in that: The composite crystal nucleating agent is composed of the following ingredients: talc, aluminum sorbate, silane coupling agent, dispersant, co-plasticizer and ultraviolet absorber, wherein the ratio of talc, aluminum sorbate, silane coupling agent, dispersant, co-plasticizer and ultraviolet absorber is 2:5:4:6:5:

2.

4. The corrosion-resistant glass fiber composite material according to claim 3, characterized in that: The silane coupling agent is KH-550 and KH-560, the molar ratio of KH-550 to KH-560 is 2.09:1, the dispersant is any one or more of low molecular weight polyethylene wax and stearic acid, and the auxiliary plasticizer is sodium tripolyphosphate.

5. A method for preparing a corrosion-resistant glass fiber composite material, characterized in that: The following steps are involved: Step S1: putting glass fiber, Kevlar fiber and glass fiber chopped strand mat into an oven for drying to remove moisture, the drying temperature is set to 110° C., the drying time is 2.5 hours, and after drying, the fiber material is stored in a sealed bag to obtain a raw material matrix A; Step S2: surface treating the raw material matrix A prepared in step S1 with a silane coupling agent, soaking the raw material matrix A in the silane coupling agent solution for 30 minutes, then taking it out and drying it, to obtain a raw material matrix B; Step S3: crushing the bamboo fiber to prepare 1-3 mm bamboo fiber, soaking the bamboo fiber in an alkaline solution for 2-3 hours to remove impurities and lignin in the bamboo fiber, and then washing the bamboo fiber with clean water until the pH value of the washing solution is neutral, and finally drying the bamboo fiber at a drying temperature of 80° C. to 90° C. for 2.5-3.5 hours; Step S4: adding aluminum oxide, carbon nanotubes and graphene to a dispersion medium and then placing them in an ultrasonic disperser, and adding sodium dodecylbenzene sulfonate as a surfactant, and performing a dispersion operation, with an ultrasonic power of 600-800 W and a dispersion time of 45-60 minutes; Step S5: adding phenolic epoxy vinyl ester resin to a reaction kettle, heating to 90° C., and when the material has fluidity, sequentially adding hydroxymethyl cellulose, diisononyl phthalate, antioxidant, and coupling agent, and stirring at a speed of 400-600 r / min for 40-60 minutes; Step S6: adding the dispersed alumina, carbon nanotubes, and graphene filling materials into the reactor, continuing to stir at a speed of 400-600 r / min for 25-30 minutes, then adding the composite crystal nucleating agent, and continuing to stir for 18-25 minutes; Step S7: adding the dried glass fiber, Kevlar fiber, glass fiber chopped strand mat and pretreated bamboo fiber into the reactor, while increasing the stirring speed to 900 r / min for 50-70 minutes; Step S8: pouring the mixed material into a mold and molding the material using a compression molding process.

6. The method for preparing a corrosion-resistant glass fiber composite material according to claim 5, characterized in that: The dispersion medium in step S4 is ethanol, and the upper liquid level of ethanol is higher than the top of the mixture of aluminum oxide, carbon nanotubes and graphene. The addition amount of sodium dodecylbenzene sulfonate is 0.5%-1% of the total mass of the filling material.

7. The method for preparing a corrosion-resistant glass fiber composite material according to claim 5, characterized in that: The composite crystal nucleating agent in step S5 comprises the following preparation steps: Step A1: adding talcum powder and aluminum sorbate into a reaction kettle, stirring at 40° C. and 500 r / min for 10 minutes to preliminarily mix the two, and obtaining an intermediate nucleating agent B; Step A2: adding KH-550 and KH-560 silane coupling agents into the reaction kettle, stirring while adding, the adding time is controlled to be about 15 minutes, the mixing control system controls the temperature to be maintained at 40° C., the stirring speed remains unchanged, and stirring is continued for 20 minutes to allow the silane coupling agent to fully contact with talc and aluminum sorbate; Step A3: adding the dispersant and sodium tripolyphosphate into the reaction kettle, keeping the temperature constant, controlling the stirring speed to 800 r / min by the mixing control system, stirring for 25 minutes, and ensuring that the dispersant and the auxiliary plasticizer are evenly dispersed in the mixture; Step A4: Add the ultraviolet absorber into the reaction kettle, and continue stirring at 60°C and 800r / min for 15 minutes to fully integrate the ultraviolet absorber into the mixture to obtain a composite crystal nucleating agent.

8. The method for preparing a corrosion-resistant glass fiber composite material according to claim 7, characterized in that: The mixing control system includes a temperature control module, a stirring control module, a component monitoring module, an intelligent control module and an alarm module. The temperature control module includes a temperature detector, a heating mechanism and a cooling mechanism. The stirring control module includes a motor and a speed regulation mechanism and a stirring mechanism. The component detection module is composed of a component detector. The intelligent control module includes a data processing unit and a control instruction unit. The alarm module includes a sensor fault detection unit and an alarm.

9. The method for preparing a corrosion-resistant glass fiber composite material according to claim 8, characterized in that: The specific control method of the hybrid control system is as follows: Step 1: When talcum powder and aluminum sorbate are mixed, the temperature of the reactor is set to 40°C, the intelligent control module starts the heating device, and the temperature of the reactor is gradually increased to 40°C. The temperature detector feeds back the temperature data in real time. When the temperature reaches 40°C, the control system maintains the heating power stable to compensate for the heat loss and keep the temperature constant. The stirring device is started at a speed of 500r / min, and the stirring is continued for 10 minutes to make the two preliminarily mixed evenly. During this process, the temperature and stirring speed are monitored in real time to stabilize them at the set value. At the same time, the component detector starts to work to monitor the stirring uniformity; Step 2: When adding KH-550 and KH-560 silane coupling agents, stir while adding, control the addition time to 15 minutes, maintain the reactor temperature at 40°C, keep the stirring speed unchanged, and continue stirring for 20 minutes to allow the silane coupling agent to fully contact with talc and aluminum sorbate. During this period, the temperature sensor continuously monitors the temperature; Step 3: Add the dispersant and sodium tripolyphosphate into the reactor, keep the temperature at 40°C, increase the stirring speed to 800r / min, and stir for 25 minutes. During this process, mix and stir by increasing the stirring speed to make the dispersant and the auxiliary plasticizer evenly dispersed in the mixture, and pay close attention to the stability of the temperature and speed; Step 4: Add the UV absorber to the reactor and raise the temperature to 60°C. The intelligent control module gradually increases the heating power to raise the temperature from 40°C to 60°C. The temperature detector monitors the temperature change in real time. When the temperature reaches 60°C, the control system adjusts the heating power to maintain a stable temperature and continues stirring at a speed of 800r / min for 15 minutes to fully integrate the UV absorber into the mixture.

Citation Information

Cited By

  • Impact-resistant glass fiber composite material and preparation method thereof

    CN120289909A